2010
DOI: 10.1063/1.3437399
|View full text |Cite
|
Sign up to set email alerts
|

Influence of lanthanum doping on the morphotropic phase boundary of lead zirconate titanate

Abstract: A phase diagram for morphotropic ͑Pb 0.985 La 0.01 ͒͑Zr 1−x Ti x ͒O 3 is proposed based on a combination of X-ray and neutron powder diffraction experiments and complemented by transmission electron microscopy. Dependent on composition three regions are characterized. The stability range of tetragonal microdomains for high Ti contents, the stability range of rhombohedral microdomains for low Ti contents, and an intermediate stability range of nanodomains. All three regions exhibit a corresponding low temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 45 publications
1
28
0
Order By: Relevance
“…Figure 5 presents temperature dependence of depolarization current density J depol and piezoelectric coefficient d 33 The d 33 of PZT decreases smoother than that of BT; this might be because of the existence of low symmetry nanopolar domains in PZT. 59 Coexistence of domains of a different structure allows for less abrupt accommodation of domain structure to temperature changes.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 5 presents temperature dependence of depolarization current density J depol and piezoelectric coefficient d 33 The d 33 of PZT decreases smoother than that of BT; this might be because of the existence of low symmetry nanopolar domains in PZT. 59 Coexistence of domains of a different structure allows for less abrupt accommodation of domain structure to temperature changes.…”
Section: Resultsmentioning
confidence: 99%
“…For a comparable PZT 1La material, the diffraction intensity between the tetragonal peaks has been attributed to the presence of nanostructured domains. 31,33 The PZT 52.25/47.75 1Nb2Sr will be referred as t-morphotropic in the text.…”
Section: Introductionmentioning
confidence: 99%
“…This unexpected behavior can either be due to strain from tetragonal domain growth or an artifact resulting from the residual anisotropic reflection broadening. This effect is well known for PZT and could be related to real structure effects from the microstructure [24,25] mics starting from 20 C to 400 C using a 20 C measurement step. Chemical analysis carried out on the sample showed that small amounts of Zr were introduced during the processing and that small amount of some volatile elements (Li, K and Sb) were lost after sintering.…”
Section: Tetragonal P4mmmentioning
confidence: 99%